Advanced Engine Diagnostics - Agarwal, Avinash Kumar; Gupta, Jai Gopal; Sharma, Nikhil; Singh, Akhilendra Pratap (Energy, Environment, and Sustainability, 2019)
This book describes the discusses advanced fuels and combustion, emission control techniques, after-treatment systems, simulations and fault diagnostics, including discussions on different engine diagnostic techniques such as particle image velocimetry (PIV), phase Doppler interferometry (PDI), laser ignition. This volume bridges the gap between basic concepts and advanced research in internal combustion engine diagnostics, making it a useful reference for both students and researchers whose work focuses on achieving higher fuel efficiency and lowering emissions. .